Developmental Biology - Scott F. Gilbert (Sinauer Associates/ Oxford University Press, 2018)
A classic gets a new coauthor and a new approach: Developmental Biology, Eleventh Edition, keeps the excellent writing, accuracy, and enthusiasm of the Gilbert Developmental Biology book, streamlines it, adds innovative electronic supplements, and creates a new textbook for those teaching Developmental Biology to a new generation. Several new modes of teaching are employed in the new Gilbert and Barresi textbook. The videos explaining development-as well as those from Mary Tyler's Vade Mecum-are referenced throughout the book, and several other valuable new elements have been added.